2013
DOI: 10.1080/15332845.2013.807393
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Competencies Required of Airline Cabin Crew Members: The Case of a Korean Airline

Abstract: Airlines are eager to hire well-qualified employees because success in the airline industry depends on the service provided by cabin crews. The authors of this study aimed to identify ways to develop training programs for airline cabin crews that focus on competencies. Competency-based training, in contrast to training that centers on learning job skills and knowledge, can facilitate the individual development of cabin crew members and increase company productivity. More specifically, the authors comprehensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 42 publications
(70 reference statements)
0
18
0
1
Order By: Relevance
“…For example, an investigation of the competency requirements of incident investigators remains vital; such a study would support the development of competency-based training for investigators. This is because competency-based training has been found to be more useful, productive and to facilitate individual development in contrast to training based on learning job skills [52].…”
Section: Association Between Maturity Of Incident Investigation and Smentioning
confidence: 99%
“…For example, an investigation of the competency requirements of incident investigators remains vital; such a study would support the development of competency-based training for investigators. This is because competency-based training has been found to be more useful, productive and to facilitate individual development in contrast to training based on learning job skills [52].…”
Section: Association Between Maturity Of Incident Investigation and Smentioning
confidence: 99%
“…Researchers have studied the effectiveness of cabin crew and the influence of their behaviour on airline service quality (Chen & Chen, 2014;Kang, Jeon, Lee, & Lee, 2005;Limpanitgul, Robson, Gould-Williams, & Lertthaitrakul, 2013), as well as gender representation in the airline industry (Baum, 2012). Another sub-theme is the examination of the quality and structure of cabin crew training (Kim & Park, 2013;Rhoden, Ralston, & Ineson, 2008) and of ground service performances and issues (Lin, Wong, & Ho, 2013;Wattanacharoensil & Yoopetch, 2012), usually based on quantitative research. A second subgroup of articles explores the relationship among various air transport partners (Riege, Perry, & Go, 2002), as well as the implementation of CSR in transport and tourism, especially LCCs (Coles, Fenclova, & Dinan, 2011;, with qualitative research methods (interviews) mostly used.…”
Section: Content and Thematic Analysismentioning
confidence: 99%
“…Kim and Park (2014) in their seminal study, comprehensively sought to identify the job competencies required of airline cabin crews. Even though there has been considerable research (Curtis et al, 2012;Saha & Theingi, 2009) conducted on the relationship between employee performance and customer satisfaction, no study has probed the relationship between CBT, flight attendant performance, and customer satisfaction.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Curtis et al (2012) found that employee training was associated with profitability. Subsequently, some airlines, like Lufthansa, are actively conducting competency-based training programs (Kim & Park, 2014) to ensure that flight attendants have the requisite knowledge and skill because organizational success is contingent on the service provided by the cabin crew.…”
Section: Introductionmentioning
confidence: 99%